Influence Green Human Resource Management to Corporate Reputation and Employee Well-Being Moderated by Organizational Culture at ABC Hospital (Jurnal Manajemen Bisnis, 2025)
This study aimed to comprehensively analyze the impact of Green Human Resource Management (GHRM) practices, including green recruitment, green training, and green reward, on corporate reputation and employee well-being, considering the moderating role of organizational culture. The research involved 256 employees from the healthcare sector, with data analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings indicate that green training and organizational culture have a significant positive influence on corporate reputation. Furthermore, green recruitment, green reward, and corporate reputation significantly and positively affect employee well-being. However, green recruitment and green reward showed no significant influence on corporate reputation, and green training did not impact employee well-being. Additionally, organizational culture was unable to moderate the relationship between GHRM practices and corporate reputation. These findings provide important implications for developing more effective GHRM policies and strategies in Indonesia, particularly within the healthcare sector.